TRIF‐dependent TLR signaling, its functions in host defense and inflammation, and its potential as a therapeutic target. Issue 1 (9th May 2016) - Ullah, M. Obayed; Sweet, Matthew J.; Mansell, Ashley; Kellie, Stuart; Kobe, Bostjan
Abstract : Review of the TRIF adaptor protein's role in TLR signaling pathways, and its involvement in disease processes. Abstract : Toll/IL‐1R domain‐containing adaptor‐inducing IFN‐β (TRIF)‐dependent signaling is required for TLR‐mediated production of type‐I IFN and several other proinflammatory mediators. Various pathogens target the signaling molecules and transcriptional regulators acting in the TRIF pathway, thus demonstrating the importance of this pathway in host defense. Indeed, the TRIF pathway contributes to control of both viral and bacterial pathogens through promotion of inflammatory mediators and activation of antimicrobial responses. TRIF signaling also has both protective and pathologic roles in several chronic inflammatory disease conditions, as well as an essential function in wound‐repair processes. Here, we review our current understanding of the regulatory mechanisms that control TRIF‐dependent TLR signaling, the role of the TRIF pathway in different infectious and noninfectious pathologic states, and the potential for manipulating TRIF‐dependent TLR signaling for therapeutic benefit.